Analisis Makna dan Fungsi Syair Adat Pernikahan Etnis Sikka Krowe di Waiara Desa Wairbleler Kecamatan Waigete Kabupaten Sikka: Penelitian - Fransiska Liliana; Rimasi; Maria Ermelinda Dua Lering (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Traditional poetry at the Sikka krowe ethnic wedding ceremony is a traditional culture that contains moral values that are in accordance with people's lives. The traditional wedding ceremony is sacred and has religious value in people's lives. The poetry of the traditional wedding ceremony is symbolised by traditional poems as advice in the ceremony. Traditional poems contain moral, cultural, and belief values. The purpose of this study is to describe the meaning and function of traditional wedding poems of Sikka krowe ethnicity in Waiara, Wairbleler Village, Waigete Sub-district, Sikka Regency. The approach used is descriptive qualitative. Descriptive qualitative is an approach that aims to collect data in the form of words and images in the field by means of observation, interviews and documentation. The result of this research is that the poem has meaning, namely the meaning of intention, the meaning of prohibition, and the meaning of poetic loyalty and has an important function in people's lives, both in social, cultural, educational and spiritual.